Resuscitative Endovascular Balloon occlusion of the aorta in Impending Traumatic arrest: Is It Effective? - Jae Sik Chung; Oh Hyun Kim; Seongyup Kim; Ji Young Jang; Gyo Jin An; Pil Young Jung (Journal of Trauma and Injury)
Purpose Hemorrhagic shock is the leading cause of death in trauma patients worldwide. Resuscitative endovascular balloon occlusion of the aorta (REBOA) is a technique used to improve the hemodynamic stability of patients with traumatic shock and to temporarily control arterial hemorrhage. However, further research is required to determine whether REBOA with cardiopulmonary resuscitation (CPR) in near-arrest or arrest trauma patients can help resuscitation. We analyzed trauma patients who underwent REBOA according to their CPR status and evaluated the effects of REBOA in arrest situations. Methods This study was a retrospective single-regional trauma center study conducted at a tertiary medical institution from February 2017 to November 2019. We evaluated the mortality of severely injured patients who underwent REBOA and analyzed the factors that influenced the outcome. Patients were divided into CPR and non-CPR groups. Results We reviewed 1,596 trauma patients with shock, of whom 23 patients underwent REBOA (1.4%). Two patients were excluded due to failure and a repeated attempt of REBOA. The Glasgow Coma Scale score was lower in the CPR group than in the non-CPR group (p=0.009). Blood pressure readings at the emergency room were lower in the CPR group than in the non-CPR group, including systolic blood pressure (p=0.012), diastolic blood pressure (p=0.002), and mean arterial pressure (p=0.008). In addition, the mortality rate was higher in the CPR group (100%) than in the non-CPR group (50%) (p=0.012). The overall mortality rate was 76.2%. Conclusions Our study suggests that if REBOA is deemed necessary in a timely manner, it is better to perform REBOA before an arrest occurs. Therefore, appropriate protocols, including pre-hospital REBOA, should be constructed to demonstrate the effectiveness of REBOA in reducing mortality in arrest or impending arrest patients.